2019
DOI: 10.1088/1361-6501/ab24a3
|View full text |Cite
|
Sign up to set email alerts
|

Coupled velocity and temperature acoustic tomography in heated high subsonic Mach number flows

Abstract: The application of acoustic tomography (AT) for simultaneous velocity and static temperature estimation has generally been restricted to low subsonic Mach number applications due to the increased complexities associated with acoustic refraction, high computational resource requirements, and a limited range of practical applications. The current work describes a novel AT method for application in such conditions and presents the results of a proof of concept laboratory jet experiment. Using a traversed set of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this study, an acoustic pyrometer similar to the one proposed by DeSilva et al [7,8] was considered. Therefore, heavy-duty gas turbine exhaust was assumed to flow inside a stainless-steel pipe with a diameter of 1 m. The temperature and pressure of the turbine exhaust were supposed to be Texh = 813.15 K and pexh = 101325 Pa, respectively, whilst the gas relative humidity was considered RH = 70%.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an acoustic pyrometer similar to the one proposed by DeSilva et al [7,8] was considered. Therefore, heavy-duty gas turbine exhaust was assumed to flow inside a stainless-steel pipe with a diameter of 1 m. The temperature and pressure of the turbine exhaust were supposed to be Texh = 813.15 K and pexh = 101325 Pa, respectively, whilst the gas relative humidity was considered RH = 70%.…”
Section: Case Studymentioning
confidence: 99%
“…Furthermore, at the end of their experiment, they concluded that the chirp signal was the most robust to calculate the TOF in noisy environments. More recently, Otero et al [8] used AP to simultaneously measure jet velocity and static temperature fields in subsonic flows. In the study, they conducted a sensitivity analysis to assess the influence of different parameters on the accuracy of the reconstruction technique.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties of measuring the geometry of the flowmeter were estimated as (resulting from the meters and their capabilities): b) The type B uncertainty of ∆t in the autocorrelator, we assume an error uniformly distributed over an interval of ± 10 samples, then: (6) c) The combined uncertainty is as follows: (7) Based on all partial uncertainties, the velocity uncertainty for highest experimental line velocity was determined to be:…”
Section: Experimental Linementioning
confidence: 99%
“…In this area, it is also worth mentioning an older publication in which the authors also deal with the reconstruction of the velocity field using tomographic evaluation of the ultrasonic signal [4], [5] and [6]. The new publication [7] is also worth noting, in which the authors moved the field of application of the ultrasonic tomograph principle to the field of compressible fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…The main parameters influencing the reliability of an AP measurement are seldom investigated in the literature. For instance, Otero et al [6] investigated the impact of several measurement parameters on the estimation accuracy of temperature and velocity fields in a subsonic flow. In particular, they found that the emitter and receiver number has the main influence on temperature reconstruction resolution, accuracy and computational cost.…”
Section: Introductionmentioning
confidence: 99%